DAMPAK PROGRAM KAKAO BERKELANJUTAN TERHADAP PEMBERDAYAAN PETANI DAN PENGUATAN KELOMPOK TANI (Study Kasus pada Kelompok Tani Kakao di Kabupaten Majene, Sul-bar) - Nurliani Nurliani; Iskandar Hasan; Busmar Busmar (Percetakan Umi Toaha Makassar, 2019)
This study aims to identify the implementation of the Sustainable Cocoa Program in Majene Regency, West Sulawesi Province, to identify the impact of the Sustainable Cocoa Program on the empowerment of cocoa farmers in Majene Regency, West Sulawesi Province, to know and analyze the impact of the Sustainable Cocoa Program on strengthening farmer groups in Majene Regency, West Sulawesi Province. This research was carried out by Majene Regency. The population in this study were all farmer groups that carried out a sustainable Cocoa Program, amounting to 25 farmer groups. The determination of the research sample used a purposive sampling method, namely choosing 2 farmers (1 administrator and 1 member) from each farmer group, so that the total sample was 50 farmers. Analysis of the data used descriptively to analyze the impact of the program on strengthening farmer groups, namely conducting an R-O-N analysis (Resource-Organization, and Norm). The impact of the sustainable cocoa program on training, mentoring, seedling assistance, and work wage assistance has made farmers more active in caring for their cocoa farming. The impact of the sustainable cocoa program on training activities is that respondents carry out fertilizing, planting, spraying, harvesting, pruning, and sanitation activities that are not in accordance with the training material. The impact of the sustainable cocoa program on seedling assistance is 7,404 trees / farmer groups and capital assistance for work wages is Rp. 5,665,000 / group. The ultimate goal of a sustainable cocoa program for strengthening farmer groups is no capital fertilization, active participation in counseling, active extension workers. Classroom skills, complete organization, existing functions and roles of administrators, mutual cooperation activities already in place and existing division of tasks in farmer groups.